Revolution of the right to education - Monteiro, A. Reis (Agostinho Reis) (Brill | Sense, 2021)
"The author argues in his essay on the Revolution of the Right to Education that the birth of the human right to education, after a millennia-long gestation, has opened up a new chapter in the History of Education. Moreover, its normative, jurisprudential, doctrinal, and programmatic developments are constituents of an International Education Law that is now the highest source in the hierarchy of the contemporary normativity on education, to which the Education Law in States Parties should conform. Therefore, it should be recognised and studied as a new legal and educational discipline, the source of principles of legitimacy and quality of education. This book offers an interdisciplinary and topical introduction to the International Education Law, broadly defined. It explains in what ways the normative integrity of the right to education carries far-reaching revolutionary significance, corollary of the Revolution of Human Rights and the Revolution of the Rights of the Child"--